# Solve for y square root of y^2-3y+64=y+5 y2-3y+64=y+5
To remove the radical on the left side of the equation, square both sides of the equation.
y2-3y+642=(y+5)2
Simplify each side of the equation.
Multiply the exponents in ((y2-3y+64)12)2.
Apply the power rule and multiply exponents, (am)n=amn.
(y2-3y+64)12⋅2=(y+5)2
Cancel the common factor of 2.
Cancel the common factor.
(y2-3y+64)12⋅2=(y+5)2
Rewrite the expression.
(y2-3y+64)1=(y+5)2
(y2-3y+64)1=(y+5)2
(y2-3y+64)1=(y+5)2
Simplify.
y2-3y+64=(y+5)2
y2-3y+64=(y+5)2
Solve for y.
Simplify (y+5)2.
Rewrite (y+5)2 as (y+5)(y+5).
y2-3y+64=(y+5)(y+5)
Expand (y+5)(y+5) using the FOIL Method.
Apply the distributive property.
y2-3y+64=y(y+5)+5(y+5)
Apply the distributive property.
y2-3y+64=y⋅y+y⋅5+5(y+5)
Apply the distributive property.
y2-3y+64=y⋅y+y⋅5+5y+5⋅5
y2-3y+64=y⋅y+y⋅5+5y+5⋅5
Simplify and combine like terms.
Simplify each term.
Multiply y by y.
y2-3y+64=y2+y⋅5+5y+5⋅5
Move 5 to the left of y.
y2-3y+64=y2+5⋅y+5y+5⋅5
Multiply 5 by 5.
y2-3y+64=y2+5y+5y+25
y2-3y+64=y2+5y+5y+25
y2-3y+64=y2+10y+25
y2-3y+64=y2+10y+25
y2-3y+64=y2+10y+25
Move all terms containing y to the left side of the equation.
Subtract y2 from both sides of the equation.
y2-3y+64-y2=10y+25
Subtract 10y from both sides of the equation.
y2-3y+64-y2-10y=25
Combine the opposite terms in y2-3y+64-y2-10y.
Subtract y2 from y2.
-3y+64+0-10y=25
-3y+64-10y=25
-3y+64-10y=25
Subtract 10y from -3y.
-13y+64=25
-13y+64=25
Move all terms not containing y to the right side of the equation.
Subtract 64 from both sides of the equation.
-13y=25-64
Subtract 64 from 25.
-13y=-39
-13y=-39
Divide each term by -13 and simplify.
Divide each term in -13y=-39 by -13.
-13y-13=-39-13
Cancel the common factor of -13.
Cancel the common factor.
-13y-13=-39-13
Divide y by 1.
y=-39-13
y=-39-13
Divide -39 by -13.
y=3
y=3
y=3
Solve for y square root of y^2-3y+64=y+5

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top